Tomatine as a steroidal glycoalkaloid: Biosynthesis, bioactivities and emerging phytochemical applications - N.V. Kanimozhi; M. Sukumar (Phytochemistry Letters, 2026)

Repurposing banana sheath scutcher for soil conservation: Improving soil water holding capacity and nutrient availability - Prabhu Govindasamy; N. Celcia Jenifer; K. Sedhupathi; K.J. Jeyabaskaran; Pramod Shelake; I. Ravi; M. Loganathan; V. Sukumar; R. Selvarajan (Bioresource Technology Reports, 2026)

Molecular characterization of virulent genotype XIII Newcastle disease virus isolates from desi-chickens in Namakkal, South India - D. Malar; P. Ponnusamy; S. Saravanan; M. Sasikala; K. Sukumar (Veterinary Research Communications, 2026)

Maternal nutrition and metabolic adaptations for healthy pregnancy and fetal programming - N.V. Kanimozhi; Chinta Suneetha; L. Sonali; M.P. Drisya Raj; R. Pavithra; B. Roopa Shri; S. Ashok Kumar; R. Palpandi Raja; M. Sukumar (Food and Humanity, 2026)

Distinct amino acid substitutions in the EEV glycoprotein and DNA-dependent RNA polymerase of lumpy skin disease virus identified in wetland areas of Bangladesh - Moslema Jahan Mou; S.M. Nazmul Hasan; Anandha Mozumder; Marjana Akter; Riyan Al Islam Reshad; Roni Mia; Md. Salauddin; M. Shaminur Rahman; Md. Mahmudul Alam; Sharmin Akter; Sukumar Saha; Tofazzal Islam; et al. (Research in Veterinary Science, 2025)

Removal notice to “Development of synbiotic juice by spray drying of Lactobacillus paracaesii sub sp. tolerans N2-45 along with galacto-oligossacharides using different carrier materials” [Bioactive Carbohydrates and Dietary Fibre 31 (2024) 100413] - N.V. Kanimozhi; M. Sukumar (Bioactive Carbohydrates and Dietary Fibre, 2024)

Removed: Development of synbiotic juice by spray drying of Lactobacillus paracaesii sub sp. tolerans N2-45 along with galacto-oligosaccharides using different carrier materials - N.V. Kanimozhi; M. Sukumar (Bioactive Carbohydrates and Dietary Fibre, 2024)

Chromosome substitution lines with improved essential mineral nutrients and fiber quality traits in Upland cotton - Sukumar Saha; Haile Tewolde; Johnie N. Jenkins; Jack C. McCarty; David M. Stelly (Genetic Resources and Crop Evolution, 2023)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Alteration of root and shoot morphologies by interspecific replacement of individual Upland cotton chromosome or chromosome segment pairs - Mirzakamol S. Ayubov; Tokhir M. Norov; Sukumar Saha; Te-Ming Tseng; K. Raja Reddy; Johnie N. Jenkins; Ibrokhim Y. Abdurakhmonov; David M. Stelly (Euphytica, 2021)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Effect of chromosome substitutions from Gossypium barbadense L., G. tomentosum Nutt. Ex Seem and G. mustelinum Watt into G. hirsutum L. on cottonseed protein and oil content - Sukumar Saha; Nacer Bellaloui; Johnie N. Jenkins; Jack C. McCarty; David M. Stelly (Euphytica, 2020)

Morph-physiological responses of cotton interspecific chromosome substitution lines to low temperature and drought stresses - Akanksha Awasthi; K. Raja Reddy; Sukumar Saha; Johnie N. Jenkins; David M. Stelly (Euphytica, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Herd-level risk factors for bovine viral diarrhea infection in cattle of Tamil Nadu - Subbiah Krishna Kumar; K. M. Palanivel; K. Sukumar; B. Samuel Masilamoni Ronald; G. Selvaraju; G. Ponnudurai (Tropical Animal Health and Production, 2018)

Molecular confirmation of Gossypium hirsutum chromosome substitution lines - Sukumar Saha; David M. Stelly; Abdusalom K. Makamov; Mirzakamol S. Ayubov; Dwaine Raska; Osman A. Gutiérrez; Shivapriya Manchali; Johnie N. Jenkins; Dewayne Deng; Ibrokhim Y. Abdurakhmonov (Euphytica, 2015)

A Rapid and Miniaturized Method for the Selection of Microbial Phenol Degraders Using Colourimetric Microtitration - Mohammed A. Fayidh; Sabina Kallary; P. Azhagu Saravana Babu; M. Sivarajan; M. Sukumar (Current Microbiology, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Climate change and multitrophic interactions in soil: the primacy of plants and functional domains - Sukumar Chakraborty; Ireneo B. Pangga; Margaret M. Roper (Global Change Biology, 2012)
Soil multitrophic interactions transfer energy from plants as the predominant primary producer to communities of organisms that occupy different positions in the food chain and are linked by multiple ecological networks, which is the soil food web. Soil food web sequesters carbon, cycles nutrients, maintains soil health to suppress pathogens, helps plants tolerate abiotic and biotic stress, and maintains ecosystem resilience and sustainability. Understanding the influence of climate change on soil multitrophic interactions is necessary to maintain these essential ecosystem services. But summarising this influence is a daunting task due to a paucity of knowledge and a lack of clarity on the ecological networks that constitute these interactions. The scant literature is fragmented along disciplinary lines, often reporting inconsistent findings that are context and scale‐dependent. We argue for the differentiation of soil multitrophic interactions along functional and spatial domains to capture cross‐disciplinary knowledge and mechanistically link all ecological networks to reproduce full functionalities of the soil food web. Distinct from litter mediated interactions in detritosphere or elsewhere in the soil, the proposed ‘pathogen suppression’ and ‘stress tolerance’ interactions operate in the rhizosphere. A review of the literature suggests that climate change will influence the relative importance, frequency and composition of functional groups, their trophic interactions and processes controlling these interactions. Specific climate change factors generally have a beneficial influence on pathogen suppression and stress tolerance, but findings on the overall soil food web are inconsistent due to a high level of uncertainty. In addition to an overall improvement in the understanding of soil multitrophic interactions using empirical and modelling approaches, we recommend linking biodiversity to function, understanding influence of combinations of climatic factors on multitrophic interactions and the evolutionary ecology of multitrophic interactions in a changing climate as areas that deserve most attention.

Molecular evolution of the clustered MIC-3 multigene family of Gossypium species - Zabardast T. Buriev; Sukumar Saha; Shukhrat E. Shermatov; Johnie N. Jenkins; Abdusattor Abdukarimov; David M. Stelly; Ibrokhim Y. Abdurakhmonov (Theoretical and Applied Genetics, 2011)

Endophytic fungal communities in woody perennials of three tropical forest types of the Western Ghats, southern India - T. S. Suryanarayanan; T. S. Murali; N. Thirunavukkarasu; M. B. Govinda Rajulu; G. Venkatesan; R. Sukumar (Biodiversity and Conservation, 2011)

Genetic diversity of Macrophomina phaseolina isolates from certain agro-climatic regions of India by using RAPD markers - Bandamaravuri Kishore Babu; S. S. Reddy; Mukesh K. Yadav; M. Sukumar; Vijendra Mishra; A. K. Saxena; Dilip K. Arora (Indian Journal of Microbiology, 2010)

Genetic dissection of chromosome substitution lines of cotton to discover novel Gossypium barbadense L. alleles for improvement of agronomic traits - Sukumar Saha; Jixiang Wu; Johnie N. Jenkins; Jack C. McCarty; Russell Hayes; David M. Stelly (Theoretical and Applied Genetics, 2010)

Clustering, haplotype diversity and locations of MIC-3: a unique root-specific defense-related gene family in Upland cotton (Gossypium hirsutum L.) - Zabardast T. Buriev; Sukumar Saha; Ibrokhim Y. Abdurakhmonov; Johnie N. Jenkins; Abdusattor Abdukarimov; Brian E. Scheffler; David M. Stelly (Theoretical and Applied Genetics, 2010)

BAC-derived SSR markers chromosome locations in cotton - Yufang Guo; Sukumar Saha; John Z. Yu; Johnie N. Jenkins; Russell J. Kohel; Brian E. Scheffler; David M. Stelly (Euphytica, 2008)

Cotton (Gossypium spp.) R2R3-MYB transcription factors SNP identification, phylogenomic characterization, chromosome localization, and linkage mapping - Chuanfu An; Sukumar Saha; Johnie N. Jenkins; Din-Pow Ma; Brian E. Scheffler; Russell J. Kohel; John Z. Yu; David M. Stelly (Theoretical and Applied Genetics, 2008)

Identification of differentially expressed genes associated with cotton fiber development in a chromosomal substitution line (CS-B22sh) - Zhengdao Wu; Khairy M. Soliman; James J. Bolton; Sukumar Saha; Johnie N. Jenkins (Functional & Integrative Genomics, 2008)

Molecular and SNP characterization of two genome specific transcription factor genes GhMyb8 and GhMyb10 in cotton species - Chuan-Yu Hsu; Chuanfu An; Sukumar Saha; Din-Pow Ma; Johnie N. Jenkins; Brian Scheffler; David M. Stelly (Euphytica, 2008)

Transcriptome profiling, sequence characterization, and SNP-based chromosomal assignment of the EXPANSIN genes in cotton - Chuanfu An; Sukumar Saha; Johnie N. Jenkins; Brian E. Scheffler; Thea A. Wilkins; David M. Stelly (Molecular Genetics and Genomics, 2007)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

An additive-dominance model to determine chromosomal effects in chromosome substitution lines and other gemplasms - Jixiang Wu; Johnie. N. Jenkins; Jack C. McCarty; Sukumar Saha; David M. Stelly (Theoretical and Applied Genetics, 2006)

Non-native Intermediate Conformational States of Human Growth Hormone in the Presence of Organic Solvents - Muppalla Sukumar; Sacha M. Storms; Michael R. De Felippis (Pharmaceutical Research, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)